Estimation of drift in the application of pesticides in Conilon coffee - Crause, Déborah Hoffmam; Vitória , Edney Leandro da; Soela, Debora Moro; Oliveira, Diego Alves de; Batista, Aclécia Gonçalves; Lacerda, Elcio das Graça (Brazilian Journal of Production Engineering, 2020)
The spraying of pesticides on coffe in England has many factors that can affect the quality of targetless deposition and increase the risk of drift. The objective was to evaluate a derivative generated by hydropneumatic spraying in the culture of conilon coffe. Use 200 L hydropneumatic sprayer, pulled and driven by a tractor. In the application, a water marker solution is used, containing water and Bright Blue dye at a concentration of 400 g ha-1. Collectors were positioned at ground level according to ISO 22866 and wires of distances at different distances and heights, in addition, leaves were collected from the plagiotropic branch of the plant, in the upper and upper median to determine the spray deposition. After spraying and drying the dye, collectors, wire strands and leaves were collected and conditioned, all items are identified according to the plant height in relation to how sheets. A deposition estimate was performed using spectrophotometry. The highest percentage of exoderative found in the polyethylene collectors occurred up to a distance of 15.0, in relation to the last sprayed line, a deposition of the wire strands decreased according to the distance from the sprayed area and how the lower parts were more shows deposition.
Keywords: application technology, hidropneumatic, dispersion of drops, Coffea canephora